Bioelectrochemical Systems (BESs) Technology for The Production of Electrical Energy from Kepok Banana Stem - Chadijah, Sitti; Firnanelty, Firnanelty; Baharuddin, Maswati Baharuddin; Sappewali, Sappewali (Indonesian Journal of Chemical Research, 2023)
Bioelectrochemical Systems (BES) technology is a method for generating electric energy using bacteria as catalysts. The electricity is produced by Microbial Fuel Cells (MFCs), which represent the latest development in biological energy research. This study utilized substrates from banana stems and the bacterium Pseudomonas sp. The research aims to assess the potential of banana stems as a substrate in the MFC system and to determine the effects of adding a combination of an electrolyte solution and an appropriate buffering material to achieve maximum current, potential difference, and power density values. The results showed that the maximum current and potential difference achieved were 1.05 mA and 0.62 V, respectively, with a power density value of 446 mW/m². When combining the KMnO4 electrolyte solution with sodium phosphate buffer, a potential difference of 0.76 V and a current of 1.75 mA were obtained, resulting in a power density value of 911 mW/m². By using the K3[Fe(CN)6] electrolyte solution buffer with potassium phosphate buffer, a current of 1.14 mA was produced, and the power density value reached 406 mW/m².